Biophysical impacts of northern vegetation changes on seasonal warming patterns - Lian, Xu; Jeong, Sujong; Park, Chang-Eui; Xu, Hao; Li, Laurent Z. X.; Wang, Tao; Gentine, Pierre; Penuelas, Josep; Piao, Shilong (Nature Publishing Group, 2022)
The seasonal greening of Northern Hemisphere (NH) ecosystems, due to extended growing periods and enhanced photosynthetic activity, could modify near-surface warming by perturbing land-atmosphere energy exchanges, yet this biophysical control on warming seasonality is underexplored. By performing experiments with a coupled land-atmosphere model, here we show that summer greening effectively dampens NH warming by -0.15 +/- 0.03 degrees C for 1982-2014 due to enhanced evapotranspiration. However, greening generates weak temperature changes in spring (+0.02 +/- 0.06 degrees C) and autumn (-0.05 +/- 0.05 degrees C), because the evaporative cooling is counterbalanced by radiative warming from albedo and water vapor feedbacks. The dwindling evaporative cooling towards cool seasons is also supported by state-of-the-art Earth system models. Moreover, greening-triggered energy imbalance is propagated forward by atmospheric circulation to subsequent seasons and causes sizable time-lagged climate effects. Overall, greening makes winter warmer and summer cooler, attenuating the seasonal amplitude of NH temperature. These findings demonstrate complex tradeoffs and linkages of vegetation-climate feedbacks among seasons. The seasonal greening of Northern Hemisphere ecosystems due to extended growing periods and enhanced photosynthetic activity is, via experiments, shown to modify near-surface warming by perturbing land-atmosphere energy exchanges.